Dielectric Properties of Zr substituted Barium Strontium Titanate. (2016) - Alkathy, Mahamoud S.; Joseph, Andrews; James Raju, K.C.
Abstract: The correlation between the dielectric properties and the structural characteristics of Zr substituted Ba0.6 Sr0.4 TiO3 (Barium Strontium Titanate) ceramics were investigated under different sintering conditions in this work. (Ba0.60 Sr0.40 Zry Ti1−y O3 ) (y =0.1, 0.15 and 0.2) nanosized powders is synthesized by conventional solid state reaction method. The formation of (Ba0.60 Sr0.40 Zry Ti1−y O3 ) was confirmed by XRD. The X-ray analysis reveals that all synthesized Ba0.60 Sr0.40 Zry Ti1−y O3  powders have a cubic perovskite structure. The influence of Zr content doping on the grain size and dielectric properties of BST, including dielectric constant and loss tangent were investigated. FE- SEM images show that, the average particle size is reduced with increasing Zr content and the average grain size is in the range 100–200 nm and the well dispersed nano powders have narrow grain size distribution. Dielectric characteristics were measured using Impedance Analyser over a range of frequencies (1kHz to 1MHz). The results show that, the dielectric constant has enhanced with doping of Zr whereas the loss tangent decreases. The particular composition is an excellent candidate for supercapacitor applications. The reduction in loss for Zr doped samples may be due to reduction in vacancy concentration and fine grain size of BST ceramic resulting in its excellent dielectric properties.